A future directions of renal cell carcinoma treatment: combination of immune checkpoint inhibition and carbon ion radiotherapy - Zheng, Zhouhang; Yang, Tianci; Li, Yixuan; Qu, Pei; Shao, Zhiang; Wang, Yuan; Chang, Wei; Umar, Shahzad Muhammad; Wang, Jufang; Ding, Nan; Wang, Wei (Frontiers in Immunology, 2024)
Renal cell carcinoma (RCC) is considered radio-and chemo-resistant. Immune checkpoint inhibitors (ICIs) have demonstrated significant clinical efficacy in advanced RCC. However, the overall response rate of RCC to monotherapy remains limited. Given its immunomodulatory effects, a combination of radiotherapy (RT) with immunotherapy is increasingly used for cancer treatment. Heavy ion radiotherapy, specifically the carbon ion radiotherapy (CIRT), represents an innovative approach to cancer treatment, offering superior physical and biological effectiveness compared to conventional photon radiotherapy and exhibiting obvious advantages in cancer treatment. The combination of CIRT and immunotherapy showed robust effectiveness in preclinical studies of various tumors, thus holds promise for overcoming radiation resistance of RCC and enhancing therapeutic outcomes. Here, we provide a comprehensive review on the biophysical effects of CIRT, the efficacy of combination treatment and the underlying mechanisms involved in, as well as its therapeutic potential specifically within RCC.